Assessment of yield loss of wheat cultivars caused by Heterodera filipjevi under field conditions. Issue 5 (27th February 2018) - Karimipour Fard, Hadi; Pourjam, Ebrahim; Tanha Maafi, Zahra; Safaie, Naser
Abstract: Among the cereal cyst nematodes, Heterodera filipjevi is the dominant species of Cereal cyst nematodes (CCNs) in most cereal growing areas of Iran. To evaluate the impact of H. filipjevi on wheat cultivars, a field trial was performed in two infested fields in Isfahan province, Iran 2014 and 2015. The trials were conducted in a factorial experiment based on the complete randomized block design. The treatments consisted of three winter wheat cultivars (Back‐cross Rowshan, Pishtaz and Parsi) which were planted with and without applying nematicide aldicarb Each cultivar was planted in 6 m 2 (2 × 3 m) plots which were replicated five times. The nematode reproduction factor was calculated after determining the initial and final population of H. filipjevi in each plot before sowing the seeds and after harvesting. The grain yields and growth parameters were recorded and the variables of 2 years experiment evaluated by linear regression analysis. Cultivar × nematicide treatment combinations in the first and second years showed that H. filipjevi significantly affected grain yield and growth parameters in all three cultivars. The results revealed significant reduction of grain yield by 24.8%, 24.8% and 20.4% in Back‐cross Rowshan, Pishtaz and Parsi cultivars, respectively. The nematode reproduction factor ranged from 0.32 to 1.76 in plots plus and minus nematicide application, respectively. The analysis showed linear inverse relationships between the initial population ( Pi ) and the yields of wheat cultivars in check plots without aldicarb application.